2018
DOI: 10.4236/msa.2018.92016
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Optical Characterization of Palm Fiber Reinforced Acrylonitrile Butadiene Styrene Based Composites: Band Gap Studies

Abstract: The composite materials are replacing the conventional materials, owing to their excellent properties. The developments of new materials are on the anvil and are thriving day by day. Natural fiber composites such as palm fiber (PF) polymer composites became more enchanting because of their high specific strength, low weight and biodegradability. Mixing of natural fiber like PF with acrylonitrile butadiene styrene (ABS) polymer is finding increased applications. In this work, PF reinforced ABS composites PF-ABS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…and widely used reinforcing natural fibers are jute, cotton, sisal, banana, hemp, flex, palm etc. [1][2][3][4][5][6][7][8]. The matrix materials, polymer boardly can be classified in to thermosplasctis and thermoset polymer.…”
Section: Introductionmentioning
confidence: 99%
“…and widely used reinforcing natural fibers are jute, cotton, sisal, banana, hemp, flex, palm etc. [1][2][3][4][5][6][7][8]. The matrix materials, polymer boardly can be classified in to thermosplasctis and thermoset polymer.…”
Section: Introductionmentioning
confidence: 99%
“…The main reason for this result may be due to the inclusion of lignin in the untreated fiber, which could absorb UV- radiation and works as a UV absorber in addition to the presence of MAPE, which also reduces the absorbance. 5658…”
Section: Resultsmentioning
confidence: 99%
“…The main reason for this result may be due to the inclusion of lignin in the untreated fiber, which could absorb UV-radiation and works as a UV absorber in addition to the presence of MAPE, which also reduces the absorbance. [56][57][58] From UV-Vis in Figure 14 it can be noted that, the absorption is greatly reduced with the addition of 2.5% CB to the composites as a stabilizer against the UV radiation. It was reported that the CB absorbs light from the entire range of the solar spectrum and protects the interior of the plastic from the penetration of high-energy photons.…”
Section: Uv-vismentioning
confidence: 99%
“…A complete spectra for ABS in the range 200–1000 nm is provided by Neher et al . but again for the pure material [ 26 ]. As already discuss for PLA, also for ABS we have a lack of information about the spectral characteristics of the printed material.…”
Section: Discussionmentioning
confidence: 99%
“…The absorbance of the pure ABS in the UV-visible range (200-600 nm) is quite low [23,24], while in the range 1050-1350 nm, it was shown that the reflectance is high (>0.85) [25]. A complete spectra for ABS in the range 200-1000 nm is provided by Neher et al but again for the pure material [26]. As already discuss for PLA, also for ABS we have a lack of information about the spectral characteristics of the printed material.…”
Section: Plos Onementioning
confidence: 98%